PEMBELAJARAN BERBASIS PEMANFAATAN SUMBER BELAJAR - Ramli Abdullah (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2012)
Learning sources play important roles in solving the learning problem. They are commonly identified as messages, people, material, tool, technique, and setting. To achieve a maximum output, it is needed to develop learning sources which are managed systematically, certifiably, and functionally. The use of various learning sources in many educational institution is indeed always influenced by some factors such as internal factor which dominantly influences the teaching learning process. It can be in the form of awareness, motivation, attitude, aptitude, metacognition, ability, skill, and the user comfortness. Another factor is called external one which influences the availability of various learning sources, its quantity, accessibility, the teaching learning process, room, human resources, also tradition and the school system. Teacher and students at schools admitted that the learning sources in their school are still limited, therefore it is needed a serious efforts to provide them.